The Effect of Management Practices on Improving the Quality of Services Through Integrated Infrastructure Practices of EFQM and Six Sigma Public Health Center in Jambi Province - Dwi Noerjoedianto; Andy Amir; Andi Subandi (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
This study aims to analyze the effect of management practices on improving service quality through the practice of integrated infrastructure EFQM and Six Sigma Public Health Center (PHC) in Jambi Province. This research is a quantitative research using a cross sectional design approach through two stages of research. The research data was obtained using a questionnaire from a sample of 560 civil servant employees in 24 PHCs that were randomly selected and analyzed by second order using Smart-PLS 3.0. The results of the study found that the implementation of management practices, infrastructure practices had a fairly good average by employees and each had a direct effect on the quality of PHC services. The practice of core infrastructure is able to partially mediate between management practices and the quality of PHC services. However, in practice, not all PHCs have implemented quality management practices.